Knowledge and Awareness about Research Ethics and Ethics Committees among Engineers - S Bhuvaneshwari, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Knowledge and Awareness about Research Ethics and Ethics Committees among Engineers